Design, Synthesis, and Antitumor Activities Study of Stapled A4K14-Citropin 1.1 Peptides - Wang, Nan; Xie, Gang; Liu, Chao; Cong, Wei; He, Shipeng; Li, Yinghua; Fan, Li; Hu, Hong-Gang (Frontiers in Chemistry, 2020)
A4K14-citropin 1.1 is a structurally optimized derivative derived from amphibians' skin secreta peptide Citropin, which exhibits broad biological activities. However, the application of A4K14-citropin 1.1 as a cancer therapeutic is restricted by its structural flexibility. In this study, a series of all-hydrocarbon stapled peptides derivatives of A4K14-citropin 1.1 were designed and synthesized, and their chemical and biological characteristics were also investigated. Among them, A4K14-citropin 1.1-Sp1 and A4K14-citropin 1.1-Sp4 displayed improved helicity levels, greater protease stability, and increased antitumor activity compared with the original peptide, which establishes them as promising lead compounds for novel cancer therapeutics development. These results revealed the important influence of all-hydrocarbon stapling side chain on the secondary structure, hydrolase stability, and biological activity of A4K14-citropin 1.1.